Evaluasi Pelaksanaan Kebijakan Santunan Kematian berdasarkan PERWAKO Padang Nomor 12 Tahun 2015 - Rezi Pebratama; M Fachri Adnan; Adil Mubarak (Faculty of Social Science, Universitas Negeri Padang, 2019)
This study aimed to evaluate the implementation of the life insurance policy in Padang City. This study is based on a number of problems, namely that there were still many poor people in Padang City did not know the implementation of the Life Insurance Policy. There were still many poor people in Padang City did not have a Community Health Insurance Card or Regional Health Insurance as one of the conditions for obtaining the life insurance funds. This study was a descriptive with qualitative approach. The informants in this study were determined through purposive technique. Data were collected through observation, interview and documention studies. The results of this study indicated that the implementation of the life insurance policy has not been effective, based onpolicy evaluation indicators used by William Dunn, that is the maximization in goal achievement, efficiency in implementation effort, community satisfaction for government policy, equal distribution. The life insurancefunds has been distributed evenly, the community supported the life insurance policy, and the life insurance policy is right to be implemented among community in Padang City.